Do environmental costs and environmental information disclosure effect on environmental performance? - Adyaksana, Rahandhika Ivan; Putri, Anandita Zulia; Saputra, Era Trianita (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2022)
There are still many companies in Indonesia that do not pay attention to environmental performance. Environmental disclosure performance is currently mandatory disclosure, so it is mandatory for go public companies to disclose their environmental performance as a manifestation of the company's responsibility for the activities it carries out. This study aims to determine the effect of environmental costs and environmental information disclosure on environmental performance in manufacturing companies listed on the Indonesia Stock Exchange from 2015-2019. The research sampling technique used purposive sampling method with data analysis using the Structural Equation Modeling method. The software used is partial least square with the Warp-PLS analysis tool. The results of testing the first hypothesis show that environmental costs have a positive and insignificant effect on environmental performance, while the second hypothesis shows that environmental information disclosure has a positive and significant effect on environmental performance. This research is important to do as a study material for the manufacturing industry related to environmental performance